2021
DOI: 10.1159/000519056
|View full text |Cite
|
Sign up to set email alerts
|

Euploid First-Trimester Cystic Hygroma: A More Benign Entity than Previously Thought?

Abstract: <b><i>Objective:</i></b> Studies summarizing the outcome of first-trimester septated cystic hygroma are generally based on small studies or from multiple centers with limited ascertainment. We reviewed the natural history of a large cohort of such cases from a single tertiary referral center, with the aim being to establish contemporary outcome data, particularly in the setting of normal karyotype. <b><i>Methods:</i></b> A retrospective cohort study from 2007 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
9
1
Order By: Relevance
“…These data have led to increased knowledge regarding the ominous first-trimester sonographic finding of first-trimester septated cystic hygroma. 82 In addition, recently published data regarding 410 cases of first-trimester septated cystic hygroma from among 110,000 pregnancies in Ireland, have confirmed associated abnormal chromosomal findings among such fetuses and an increased likelihood of structural anomalies among euploid fetuses with first-trimester septated cystic hygroma. 83 In a study of 134 cases of first-trimester septated cystic hygroma (generated from the FASTER Trial Research Consortium data (among 38,167 screened patients)) Malone et al in 2005, reported 132 patients with complete follow up.…”
Section: Fetal/neonatal Outcome In Pregnancies Complicated By the Pre...mentioning
confidence: 92%
See 4 more Smart Citations
“…These data have led to increased knowledge regarding the ominous first-trimester sonographic finding of first-trimester septated cystic hygroma. 82 In addition, recently published data regarding 410 cases of first-trimester septated cystic hygroma from among 110,000 pregnancies in Ireland, have confirmed associated abnormal chromosomal findings among such fetuses and an increased likelihood of structural anomalies among euploid fetuses with first-trimester septated cystic hygroma. 83 In a study of 134 cases of first-trimester septated cystic hygroma (generated from the FASTER Trial Research Consortium data (among 38,167 screened patients)) Malone et al in 2005, reported 132 patients with complete follow up.…”
Section: Fetal/neonatal Outcome In Pregnancies Complicated By the Pre...mentioning
confidence: 92%
“…These authors concluded that first-trimester cystic hygroma is a frequent finding in a general obstetric screening program. 82 This sonographic finding exhibited the strongest prenatal association with aneuploidy hitherto, with significantly worse outcome in comparison with simple increased nuchal translucency thickness (NT). The majority of pregnancies with normal evaluation at the completion of the second trimester resulted in a healthy infant with a normal neonatal outcome.…”
Section: First-trimester Septated Cystic Hygromamentioning
confidence: 95%
See 3 more Smart Citations